Pengaruh Latihan Interval Terhadap Tendangan Dollyo Chagi Atlet Taekwondo Kab. Luwu - Resa Amalia; Rachmat Hidayat; Nasriandi Nasriandi (Jurnal Porkes, 2026)
The main problem in this study is the low proficiency in the dollyo chagi kick among Taekwondo athletes in Luwu Regency, as indicated by suboptimal kick power, speed, and endurance. The purpose of this study was to analyze the effect of interval training on improving the dollyo chagi kick proficiency of Taekwondo athletes in Luwu Regency. The method used was a quantitative approach with a one-group pretest-posttest experimental design. The sample consisted of 15 athletes aged 13–17 years, selected using purposive sampling. The research instrument was a 30-second dollyo chagi kick test to measure kick speed and power. Data were analyzed using descriptive statistics and a paired-sample t-test with the aid of SPSS version 27. The results showed an increase in the mean score from 29.80 at the pretest to 34.87 at the posttest, with a difference of 5.07 points. The results of the paired-sample t-test showed that the calculated t-value of 16.874 was greater than the critical t-value of 2.145, with a significance level of 0.001 (< 0.05), Thus, interval training has been shown to have a significant effect. The conclusion of this study is that interval training is effective in improving the power and speed of the dollyo chagi kick in Taekwondo athletes. Therefore, this method is recommended for integration into routine training programs to support the continuous improvement of athletes’ performance.